Fructose Consumption During Pregnancy Influences Milk Lipid Composition and Offspring Lipid Profiles in Guinea Pigs - Smith, Erin Vanessa LaRae; Dyson, Rebecca Maree; Berry, Mary Judith; Gray, Clint (Frontiers in Endocrinology, 2020)
Excess dietary fructose is a major public health concern (Bidwell 2017; Lustig, Schmidt, and Brindis 2012; Dekker et al. 2010; Basciano, Federico, and Adeli 2005). Evidence shows increased fructose intake can cause insulin resistance, hepatic de novo lipogenesis, hypertriglyceridemia, obesity and non-alcoholic fatty liver disease (NAFLD) (Havel 2005; Stanhope and Havel 2010; Ter Horst and Serlie 2017; Khitan and Kim 2013; Zhang, Jiao, and Kong 2017). However, little is known about the effects of fructose during pregnancy and its influence on offspring development and predisposition to later-life disease. To determine whether moderately increased maternal fructose intake could have health consequences on offspring, we have investigated the effects of 10% w/v fructose water intake during preconception and pregnancy. Female Dunkin Hartley guinea pigs were fed a control diet (CD) or fructose diet (FD;10% kcal from fructose) ad-libitum 60 days prior to mating and throughout gestation. Offspring were culled at weaning, day 21 (d21). Compared to CD dams, FD dams had altered glucose metabolism and increased milk free fatty acid content. Matsuda-DeFronzo insulin sensitivity index (M-ISI) from OGTT plasma showed no significant difference in whole-body insulin sensitivity between FD and CD dams 60 days post-dietary intervention and during midgestation. Fetal exposure to increased maternal fructose resulted in offspring with significantly altered serum free fatty acids at day 0, 7, 14 and 21 (including pentadecanoic acid (15:0), dma16:0, margaric acid (17:0) palmitoleic acid, total omega-7 and total saturates), increased levels of uric acid and triglycerides were also observed at d21. We have demonstrated that increased fructose intake during pregnancy can cause significant changes in maternal metabolic function and milk composition, which alters offspring metabolism. Taken together, these changes in pregnancy outcomes and feto-maternal condition may underlie their offspring’s predisposition to metabolic dysfunction during later-life.